Tenth Grade Students’ Ability in Writing Descriptive Text Using Magic Card - Nurhayati Nurhayati; Sayit Abdul Karim; Budiarti Budiarti; Suryo Sudiro (Universitas Muhammadiyah Kalimantan Timur, 2022)
English language teachers nowadays are challenged to present interesting and innovative ways of teaching English in order to motivate their students to learn. Magic card can be used as an alternative learning medium toward the students’ ability to write descriptive text. The present study attempts to figure out students’ ability in writing descriptive text utilizing magic card and to describe the students’ perceptions about the use of magic card in writing descriptive text. Therefore, a quantitative descriptive research design was applied. Furthermore, to obtain the data needed, a set of test and questionnaire were administered to 36 participants (29 females and 7 males) of the tenth-grade students. The findings revealed that the total mean of students’ ability was categorized into good criteria (84%). It means that the students’ ability in writing descriptive text is significantly improved. Moreover, the results of questionnaire showed that students like using magic card because magic card is an interesting medium which would make students enjoy in studying, active in writing and creative in thinking. Besides, magic card can enrich students’ vocabulary as it promotes students’ creativity.